2006
DOI: 10.1007/s10310-005-0175-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-term growth analyses of Japanese cedar trees in a plantation: neighborhood competition and persistence of initial growth deviations

Abstract: The individual growth of tree diameter at breast height (dbh) is analyzed in an even-aged plantation of Cryptomeria japonica from stand age of 45 to 94 years, to examine how the growth of individual trees has been affected by the changes in spacing resulting from thinning operations. At any age, a significant proportion (0.37-0.46) of the variation in dbh growth during a 5-11-year period was explained by dbh at the beginning of the period, probably due to greater leaf mass of larger trees. Next, either one-sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 20 publications
3
23
1
Order By: Relevance
“…Osumi et al (2000) and Nishizono et al (2008) also reported that the mean annual volume increment curve was relatively flat near and beyond culmination. In addition, several studies have reported that old-aged Japanese cedar trees were able to respond to increased resource availability following reduction in stand density by thinning (Kunisaki et al 1999;Osumi et al 2000;Masaki et al 2006;Nishizono et al 2006;Sawata et al 2007). Apparently, thinning is effective among old-aged Japanese cedar trees.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Osumi et al (2000) and Nishizono et al (2008) also reported that the mean annual volume increment curve was relatively flat near and beyond culmination. In addition, several studies have reported that old-aged Japanese cedar trees were able to respond to increased resource availability following reduction in stand density by thinning (Kunisaki et al 1999;Osumi et al 2000;Masaki et al 2006;Nishizono et al 2006;Sawata et al 2007). Apparently, thinning is effective among old-aged Japanese cedar trees.…”
Section: Introductionmentioning
confidence: 92%
“…Recognition of this fact has led to some recent studies on growth of stands and individual trees in old-aged Japanese cedar forests (e.g., Kunisaki et al 1999;Osumi et al 2000;Masaki et al 2006;Nishizono et al 2006Nishizono et al , 2008Sawata et al 2007). Osumi et al (2000) and Nishizono et al (2008) reported that stands in the Akita District of northeastern Japan seldom reached culmination of mean annual volume increment until they were 60-years old.…”
Section: Introductionmentioning
confidence: 96%
“…Several studies have examined neighborhood competition, and suggested approximately 10 m might be the critical range to be affected by neighboring trees (e.g., Nishimura et al 2003;Masaki et al 2006). In this study, we therefore examined the effects of planted trees on naturally regenerated broad-leaved trees and the effects of canopy trees on subcanopy trees for broad-leaved species simultaneously in a 10 9 10 m cell unit.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, long-rotation management is becoming increasingly widespread as it results in the production of larger and more valuable timber and is a way of hedging against fluctuations in the price of timber [37,38]. Long-rotation plantations have been observed to maintain and increase species diversity and develop stand structure better than standard-rotation plantations [39,40].…”
Section: Studies On Plant Species Diversity and Species Richness In Pmentioning
confidence: 99%